Laminated body for organic EL display and circularly polarizing plate used therein
By adopting a specific laminated structure circular polarizing plate in an organic EL display device, combining a polyvinyl alcohol-based resin film and a phase difference plate, the deterioration problem of the display device under glass protection is solved, and excellent display characteristics, bending and Durability.
Patent Information
- Application Number
- CN202010076116.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-25
- Filing Date
- 2020-01-22
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2040-01-22
AI Technical Summary
The organic EL display device is susceptible to water vapor and oxygen without glass protection, resulting in deterioration. At the same time, the circular polarizer needs to be thinned to maintain good bending, but it is difficult to ensure both display characteristics and durability.
A circular polarizing plate with a laminated structure includes a polarizing plate and a phase difference plate. The polarizing plate is made of a polyvinyl alcohol resin film, and a protective film is added to the reverse side of the phase difference plate surface of the polarizing plate, and a specific adhesive layer is passed. Combined with an optical compensation plate, the transmittance and phase difference of light are controlled to achieve excellent display characteristics, bending and durability.
Even without glass protection, excellent display characteristics, bending properties and long-term durability of the organic EL display device are achieved, and deterioration problems are avoided by controlling water vapor transmission and light transmission.
Smart Images

Figure BDA0002378376880000111 
Figure BDA0002378376880000141 
Figure BDA0002378376880000251
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate for an organic EL display, and more particularly to a laminate for an organic EL display including a specific circularly polarizing plate. Background Art
[0002] In recent years, along with the popularity of thin displays, displays equipped with organic EL panels (organic EL display devices) are becoming popular. As far as organic EL panels are concerned, since external light is reflected at the internal metal electrode, a problem such as a clear black display cannot be obtained is generated. In response to this problem, the reflection of external light can be suppressed and prevented by setting a circular polarizer on the viewing surface. That is, as the stacking order from the viewer, it is protective glass → circular polarizer → organic EL panel. Circular polarizers can usually be made by stacking polarizers and phase difference plates. As a polarizer, a polarizer obtained by stacking a transparent protective film on a polarizer formed by stretching a polyvinyl alcohol (PVA) film and dyeing it with iodine is generally used. As a phase difference plate, a stretched film, a λ / 4 plate obtained by orienting liquid crystal molecules, etc., is used, wherein it is preferred to use a λ / 4 plate that shows that the longer the wavelength, the greater the birefringence (inverse wavelength dispersion characteristics). In order to suppress the change in reflection hue when observed from an oblique direction, Patent Document 1 [Japanese Patent Application Publication No. 2015-163935] proposes a circularly polarizing plate further comprising a vertically aligned liquid crystal cured film obtained by polymerizing and curing rod-like liquid crystals in a vertically aligned state.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2015-163935 Summary of the invention
[0006] Problems to be solved by the invention
[0007] In organic EL display devices, studies have been conducted on using them in flexible forms and on not using glass on the outermost surface of the device. However, it is known that when an organic EL panel is driven without the barrier properties to water (water vapor) and oxygen provided by glass, degradation may occur. It is also known that in order to obtain good bendability, the circular polarizer itself needs to be thinner.
[0008] Therefore, the object of the present invention is to provide a laminate for an organic EL display comprising the following circularly polarizing plate, which can protect the organic EL panel even when there is no glass on the outermost surface, and on this basis, to provide an organic EL display device and a circularly polarizing plate used therein that are excellent in display characteristics, bendability and aging degradation.
[0009] Means for solving problems
[0010] The present invention has the following aspects:
[0011] [1] A laminate for an organic EL display, the laminate comprising a circularly polarizing plate and an adhesive layer,
[0012] The thickness of the laminate is 100 μm or less.
[0013] The circular polarizer includes a polarizer and a phase difference plate.
[0014] The polarizing plate includes a polarizer and a protective film, and the protective film is provided only on the side of the polarizer opposite to the side on which the phase difference plate is laminated.
[0015] The water vapor permeability of the circular polarizer is 100 g / m 2 / 24 hours or less, and
[0016] The transmittance of the circularly polarizing plate at 380 nm is 1% or less.
[0017] [2] The laminate for an organic EL display according to [1], wherein the polarizer is a polarizer formed of a polyvinyl alcohol-based resin film.
[0018] [3] The laminate for an organic EL display according to [1] or [2], wherein the transmittance of the circularly polarizing plate at 400 nm is 1% or less.
[0019] [4] A laminate for an organic EL display as described in any one of [1] to [3], wherein the phase difference plate comprises only one phase difference layer of a polymer containing a polymerizable liquid crystal compound, and the phase difference plate satisfies all of the following formulas (1), (2) and (3).
[0020] Re(450) / Re(550)≤1.00 (1)
[0021] 1.00≤Re(650) / Re(550) (2)
[0022] 100nm≤Re(550)≤180nm (3)
[0023] (Where Re(λ) represents the in-plane phase difference value with respect to light of wavelength λnm.)
[0024] [5] The laminate for an organic EL display according to [4], wherein the angle formed by the slow axis of the phase difference plate and the absorption axis of the polarizing plate is substantially 45 degrees.
[0025] [6] The laminate for an organic EL display according to any one of [1] to [3], wherein the retardation plate comprises a first retardation layer and a second retardation layer in order from the polarizing plate side,
[0026] The first phase difference layer and the second phase difference layer are each a polymer of a polymerizable liquid crystal compound.
[0027] The first phase difference layer satisfies the following equation (4):
[0028] The second phase difference layer satisfies the relationship of formula (3),
[0029] The phase difference plate satisfies the relationship between equations (1) and (2).
[0030] Re(450) / Re(550)≤1.00 (1)
[0031] 1.00≤Re(650) / Re(550) (2)
[0032] 100nm≤Re(550)≤180nm (3)
[0033] 200nm≤Re(550)≤300nm (4)
[0034] (Where Re(λ) represents the in-plane phase difference value with respect to light of wavelength λnm.)
[0035] [7] The laminate for an organic EL display according to any one of [1] to [6], further comprising an optical compensation plate formed of a polymer of a polymerizable liquid crystal compound satisfying the following formula (5).
[0036] -30nm≤Rth(550)≤-100nm (5)
[0037] (Rth(550) represents the in-plane phase difference in the film thickness direction with respect to light with a wavelength of 550 nm.)
[0038] [8] The laminate for an organic EL display according to any one of [1] to [6], wherein the circularly polarizing plate includes a pressure-sensitive adhesive layer having a transmittance of 10% or less at 400 nm.
[0039] [9] The laminate for an organic EL display according to any one of [1] to [7], wherein the protective film is a cycloolefin film.
[0040]
[10] The laminate for an organic EL display according to any one of [1] to [7], wherein the protective film is a polyimide film or a polyamideimide film.
[0041]
[11] A circularly polarizing plate, wherein at least a polarizing plate, an adhesive layer and a phase difference plate are stacked in this order,
[0042] The polarizing plate comprises a polarizer and a protective film, and the protective film is provided only on the side of the polarizer opposite to the side on which the phase difference plate is laminated.
[0043] The above-mentioned phase difference plate satisfies the relationship between equations (1) and (2),
[0044] The water vapor permeability of the circular polarizer is 100 g / m 2 / 24 hours or less, and
[0045] The transmittance of the circularly polarizing plate at 380 nm is 1% or less.
[0046] Re(450) / Re(550)≤1.00 (1)
[0047] 1.00≤Re(650) / Re(550) (2)
[0048]
[12] The circularly polarizing plate according to
[11] , wherein the polarizer is a polarizer formed of a polyvinyl alcohol-based resin film.
[0049]
[13] The circularly polarizing plate of
[11] or
[12] , wherein the transmittance of the circularly polarizing plate at 400 nm is less than 1%.
[0050]
[14] The circularly polarizing plate according to any one of
[11] to
[13] , wherein the transmittance of the adhesive layer at 400 nm is 10% or less.
[0051]
[15] The circularly polarizing plate according to any one of
[11] to
[14] , wherein the protective film is a cycloolefin film.
[0052]
[16] The circularly polarizing plate according to any one of
[11] to
[15] , wherein the protective film is a polyimide film or a polyamideimide film.
[0053] Effects of the Invention
[0054] The present invention can provide an organic EL display device having excellent display characteristics, bendability and aging degradation even when there is no glass on the outermost surface of the organic EL display device, and a circularly polarizing plate used therein. DETAILED DESCRIPTION
[0055] The organic EL display laminate of the present invention is a laminate laminated with a circular polarizer and an adhesive layer, and the circular polarizer includes a polarizer and a phase difference plate, and the polarizer includes a polarizer and a protective film. The polarizer has a protective film on the side of the polarizer opposite to the surface of the phase difference plate laminated. The phase difference plate can be a phase difference plate consisting of a layer of phase difference layer or a phase difference plate consisting of two layers of phase difference layers. In the case of two layers, it is sometimes referred to as the first phase difference layer and the second phase difference layer to distinguish. The polarizer and the phase difference plate are usually bonded by an adhesive layer to form a circular polarizer. The circular polarizer can be combined with an adhesive layer to form the laminate for the organic EL display of the present invention, and an optical compensation plate can be further combined. Therefore, the organic EL display laminate of the present invention can be a laminate formed by a circular polarizer and an adhesive layer, or it can be a laminate formed by bonding the optical compensation plate to the circular polarizer between the circular polarizer and the adhesive layer using another adhesive layer.
[0056] <Polarizing plate>
[0057] The polarizing plate includes a film having a function of light absorption anisotropy (hereinafter, sometimes referred to as a polarizer). The polarizer may be a stretched film to which a dichroic dye is adsorbed.
[0058] A polarizer that is a stretched film with a dichroic dye adsorbed thereon is generally manufactured through the following steps: a step of uniaxially stretching a polyvinyl alcohol resin film; a step of dyeing the polyvinyl alcohol resin film with a dichroic dye so that the film adsorbs the dichroic dye; a step of treating the polyvinyl alcohol resin film with the dichroic dye adsorbed thereon with an aqueous boric acid solution; and a step of washing the film with water after the treatment with the aqueous boric acid solution.
[0059] The polyvinyl alcohol resin can be obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith can be used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acid compounds, olefin compounds, vinyl ether compounds, unsaturated sulfonic acid compounds, and acrylamide compounds having an ammonium group.
[0060] The saponification degree of the polyvinyl alcohol resin is generally about 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal and polyvinyl acetal modified with aldehydes may also be used. The degree of polymerization of the polyvinyl alcohol resin is generally about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.
[0061] The film made of such a polyvinyl alcohol resin can be used as a raw film of a polarizing film. The method of making a polyvinyl alcohol resin into a film is not particularly limited, and the film can be made by a known method. The film thickness of the polyvinyl alcohol raw film can be, for example, about 10 to 150 μm.
[0062] The uniaxial stretching of the polyvinyl alcohol resin film can be performed before, at the same time as, or after dyeing based on the dichroic pigment. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. In addition, the uniaxial stretching can be performed in multiple stages thereof. When the uniaxial stretching is performed, the uniaxial stretching can be performed between rollers having different peripheral speeds, or the uniaxial stretching can be performed using a hot roller. In addition, the uniaxial stretching can be dry stretching performed in the atmosphere, or wet stretching performed in a state where the polyvinyl alcohol resin film is swollen with a solvent. The stretching ratio is usually about 3 to 8 times.
[0063] The polyvinyl alcohol-based resin film can be dyed with a dichroic dye by, for example, a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing a dichroic dye.
[0064] As the dichroic pigment, specifically, iodine and dichroic organic dyes can be used. As dichroic organic dyes, dichroic direct dyes formed by disazo compounds such as CI Direct Red 39 and dichroic direct dyes formed by compounds such as triazo and tetrakis azo can be cited. For the polyvinyl alcohol-based resin film, it is preferred to implement an immersion treatment in water in advance before the dyeing treatment.
[0065] When iodine is used as the dichroic dye, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing iodine and potassium iodide can generally be employed.
[0066] The content of iodine in the aqueous solution is usually about 0.01 to 1 part by mass relative to 100 parts by mass of water. In addition, the content of potassium iodide is usually about 0.5 to 20 parts by mass relative to 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40° C. In addition, the immersion time (dyeing time) in the aqueous solution is usually about 20 to 1,800 seconds.
[0067] On the other hand, when a dichroic organic dye is used as the dichroic coloring matter, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing a water-soluble dichroic dye can generally be employed.
[0068] The content of the dichroic organic dye in the aqueous solution is usually 1×10 -4 ~10 parts by mass, preferably 1×10-3 ~1 mass part, more preferably 1×10 -3 ~1×10 -2 The aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic dye aqueous solution used for dyeing is usually about 20 to 80° C. In addition, the immersion time (dyeing time) in the aqueous solution is usually about 10 to 1,800 seconds.
[0069] Boric acid treatment after dyeing with a dichroic pigment can usually be carried out by immersing the dyed polyvinyl alcohol resin film in an aqueous boric acid solution. The content of boric acid in the aqueous boric acid solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. When iodine is used as a dichroic pigment, the aqueous boric acid solution preferably contains potassium iodide, and the content of potassium iodide at this time is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. The immersion time in the aqueous boric acid solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0070] Generally, the polyvinyl alcohol-based resin film treated with boric acid can be subjected to a water washing treatment. The water washing treatment can be performed, for example, by immersing the polyvinyl alcohol-based resin film treated with boric acid in water. The temperature of water in the water washing treatment is generally about 5 to 40° C. In addition, the immersion time is generally about 1 to 120 seconds.
[0071] A drying treatment can be performed after washing to obtain a polarizer. The drying treatment can be performed, for example, using a hot air dryer or a far-infrared heater. The temperature of the drying treatment is usually about 30 to 100°C, preferably 50 to 80°C. The time of the drying treatment is usually about 60 to 600 seconds, preferably 120 to 600 seconds. By drying treatment, the moisture content of the polarizer can be reduced to a practical level. Its moisture content is usually about 5 to 20% by weight, preferably 8 to 15% by weight. When the moisture content is lower than 5% by weight, the flexibility of the polarizer is lost, and after the polarizer is dried, it is sometimes damaged or broken. In addition, when the moisture content is higher than 20% by weight, there is a possibility that the thermal stability of the polarizer will deteriorate.
[0072] The thickness of the polarizer obtained by uniaxially stretching the polyvinyl alcohol-based resin film, dyeing it with a dichroic dye, treating it with boric acid, washing it with water, and drying it as described above is preferably 5 to 40 μm, more preferably 5 to 20 μm.
[0073] The polarizing plate of the present invention is obtained by laminating a protective film via an adhesive layer only on one surface of the polarizer obtained by the above method, etc. The protective film is laminated on the side of the polarizer opposite to the surface on which the phase difference plate is laminated. The adhesive layer is formed using a known adhesive composition.
[0074] <Protective film>
[0075] The protective film refers to a substrate having transparency that can transmit light (especially visible light). The so-called transparency refers to the property that the transmittance relative to light in the range of wavelengths of 380 to 780 nm is 80% or more. As specific protective films, there can be mentioned: polyolefins such as polyethylene and polypropylene; cycloolefin resins such as norbornene polymers; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene ether, etc. From the perspective of ease of acquisition and transparency, polyethylene terephthalate, polymethacrylate, cellulose ester, cycloolefin resin or polycarbonate is preferred. Cellulose ester is obtained by esterifying part or all of the hydroxyl groups contained in cellulose and can be easily obtained from the market. Cellulose ester substrates can also be easily obtained from the market.
[0076] Examples of commercially available cellulose ester substrates include "FUJITAC film" (Fuji Photo Film Co., Ltd.), "KC8UX2M", "KC8UY", and "KC4UY" (Konica Minolto Opto Co., Ltd.).
[0077] The characteristics required by the protective film vary according to the composition of the polarizing plate, and a film with as small a phase difference as possible is generally preferred. As a film with as small a phase difference as possible, cellulose ester films such as ZeroTAC (Konica Minolto Opto Co., Ltd.) and Z-TAC (Fuji Film Co., Ltd.) without phase difference can be cited. In addition, unstretched cyclic olefin resin films are also preferred. As other preferred protective films, polyimide films, polyamide-imide films, etc. can also be cited. The surface of the non-laminated polarizing plate of the protective film can be hard-coated, anti-reflective, antistatic, etc.
[0078] In the present invention, the resin forming the protective film can be, for example, cycloolefin, polyamide having an amide bond in the molecule, gelatin compound, polyimide having an imide bond in the molecule and polyamic acid as its hydrolyzate, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylate. The transmittance at 400nm of the protective film is preferably 10% or less. When the transmittance at 400nm is 10% or less, it has the effect of suppressing the deterioration (discoloration) of the organic EL panel.
[0079] From the viewpoint of improving strength and processability, the thickness of the protective film is usually 10 to 80 μm, preferably 20 to 60 μm, and more preferably 20 to 40 μm.
[0080] <Phase difference plate>
[0081] The phase difference plate can be a stretched film that provides a phase difference by stretching a polymer, but from the viewpoint of thinning the layer of the organic EL display laminate of the present invention, it is preferably composed of a phase difference layer of a polymer containing a polymerizable liquid crystal compound that is horizontally oriented or vertically oriented. When the phase difference plate is composed of a phase difference layer, it can be only a phase difference layer, or it can include an orientation film and a substrate described later.
[0082] When the phase difference plate includes only one phase difference layer of a polymer containing a polymerizable liquid crystal compound, it is preferred that all of the following formulas (1), (2) and (3) are satisfied:
[0083] Re(450) / Re(550)≤1.00 (1)
[0084] 1.00≤Re(650) / Re(550) (2)
[0085] 100nm≤Re(550)≤180nm (3)
[0086] (Where Re(λ) represents the in-plane phase difference value with respect to light of wavelength λnm.)
[0087] The phase difference plate satisfying the above formula (1) has so-called reverse wavelength dispersion and shows excellent polarization performance. The value of Re(450) / Re(550) is preferably less than 0.93, more preferably less than 0.88, more preferably less than 0.86, preferably more than 0.80, more preferably more than 0.82. The above formula (3) is preferably 100nm≤Re(550)≤180nm, and more preferably 120nm≤Re(550)≤160nm.
[0088] It should be noted that Re (550) can be measured by the method described in the Examples.
[0089] In the circularly polarizing plate of the present invention, the angle between the slow axis of the phase difference plate and the absorption axis of the polarizing plate is preferably substantially 45°. It should be noted that in the present invention, "substantially 45°" means 45°±5°.
[0090] When the phase difference plate contains a first phase difference layer and a second phase difference layer, and each phase difference layer is a phase difference layer of a polymer which is a polymerizable liquid crystal compound, it is preferred that the first phase difference layer satisfies the relationship of the following formula (4), the second phase difference layer satisfies the relationship of the above formula (3), and the phase difference plate as a whole satisfies the relationship of the above formulas (1) and (2).
[0091] 200nm≤Re(550)≤300nm (4)
[0092] (Where Re(λ) represents the in-plane phase difference value with respect to light of wavelength λnm.)
[0093] The polymerizable liquid crystal compound (hereinafter, also referred to as "polymerizable liquid crystal compound (A)") that forms the phase difference layer refers to a liquid crystal compound having a polymerizable functional group, especially a photopolymerizable functional group. The so-called photopolymerizable functional group refers to a group that can participate in the polymerization reaction using active free radicals, acids, etc. generated by a photopolymerization initiator. As photopolymerizable functional groups, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane and oxetane are preferred, and acryloyloxy is more preferred. The liquid crystal may be a thermotropic liquid crystal or a lyotropic liquid crystal, and as a phase sequence structure, it may be a nematic liquid crystal or a smectic liquid crystal. As a polymerizable liquid crystal compound, only one type may be used, or two or more types may be used in combination.
[0094] Examples of the polymerizable liquid crystal compound (A) include compounds satisfying all of the following (I) to (IV) from the viewpoint of providing easiness of film formation and phase difference properties.
[0095] (I) is a compound having thermotropic liquid crystal properties;
[0096] (II) The polymerizable liquid crystal compound has π electrons in the long-axis direction (a).
[0097] (III) It has π electrons in a direction intersecting the long axis direction (a) [intersecting direction (b)].
[0098] (IV) D(πa) and D(πb) are in the relationship of 0≤〔D(πa) / D(πb)〕≤1,
[0099] [That is, the π electron density in the cross direction (b) is greater than the π electron density in the long axis direction (a)]
[0100] The D(πa) is the π electron density in the long axis direction (a) of the polymerizable liquid crystal compound defined by the following formula (i) when the total number of π electrons in the long axis direction (a) is N(πa) and the total number of molecular weights in the long axis direction (a) is N(Aa):
[0101] D(πa)=N(πa) / N(Aa) (i),
[0102] The D(πb) is the π electron density in the cross direction (b) of the polymerizable liquid crystal compound defined by the following formula (ii) when the total number of π electrons present in the cross direction (b) is N(πb) and the total number of molecular weights present in the cross direction (b) is N(Ab):
[0103] D(πb)=N(πb) / N(Ab) (ii).
[0104] It should be noted that, for the polymerizable liquid crystal compound (A) satisfying all of the above (I) to (IV), a nematic phase can be formed by coating on an alignment film formed by rubbing treatment and heating to a temperature above the phase transition temperature. For the nematic phase formed by the alignment of the polymerizable liquid crystal compound (A), the polymerizable liquid crystal compound is usually aligned in such a way that the long axis directions become parallel to each other, and the long axis direction becomes the alignment direction of the nematic phase.
[0105] The polymerizable liquid crystal compound (A) having the above characteristics usually exhibits reverse wavelength dispersion. As a compound satisfying the above characteristics (I) to (IV), specifically, for example, a compound represented by the following formula (I) can be cited,
[0106]
[0107] The compound represented by the above formula (I) can be used alone or in combination of two or more.
[0108] In formula (I), Ar represents a divalent aromatic group which may have a substituent. The aromatic group referred to herein refers to the following group, which is a group having a planar cyclic structure, and the number of π electrons possessed by the cyclic structure is counted as [4n+2] according to the Huckel rule. Here, n represents an integer. In the case where a ring structure is formed by including heteroatoms such as -N= and -S-, the case where the non-covalent bond electron pairs on these heteroatoms are included to satisfy the Huckel rule and thus have aromaticity is also included. In the divalent aromatic group, it is preferred to include at least one of a nitrogen atom, an oxygen atom, and a sulfur atom.
[0109] G1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom or a nitrogen atom.
[0110] L 1 and L 2 Each is independently a divalent linking group having an ester structure.
[0111] B 1 and B 2 Each is independently a single bond or a divalent linking group.
[0112] k and 1 each independently represent an integer from 0 to 3, and satisfy the relationship 1≤k+1. Here, when 2≤k+1, B 1 and B 2 , G 1 and G 2 Each may be the same as or different from each other.
[0113] E 1 and E 2 Each independently represents an alkanediyl group having 1 to 17 carbon atoms, wherein the hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and the -CH 2 - can be replaced by -O-, -S-, -Si-, -COO-. 1 and P 2 Each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0114] G 1 and G 2 Each of them is independently preferably 1,4-phenylenediyl which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, 1,4-cyclohexanediyl which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, more preferably 1,4-phenylene substituted with methyl, unsubstituted 1,4-phenylene, or unsubstituted 1,4-trans-cyclohexanediyl, and particularly preferably unsubstituted 1,4-phenylene or unsubstituted 1,4-trans-cyclohexanediyl. In addition, it is preferred that there are a plurality of G 1 and G 2At least one of them is a divalent alicyclic hydrocarbon group, and more preferably, L 1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.
[0115] L 1 and L 2 Each is independently preferably -R a1 COOR a2 -(R a1 and R a2 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms), more preferably -COOR a2-1 -(R a2-1 Represents a single bond, -CH 2 -、-CH 2 CH 2 - any one of -COO- or -COOCH 2 CH 2 -.
[0116] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 -, or -R a15 OC=OOR a16 -. Here, R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH 2 -、-CH 2 CH 2 -、-COOR a12 -1 -, or -OCOR a14-1 -. Here, R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH 2 -、-CH 2 CH 2 -Any of B. 1 and B 2Each of them is independently more preferably a single bond, -O-, -CH 2 CH 2 -、-COO-、-COOCH 2 CH 2 -, -OCO-, or -OCOCH 2 CH 2 -.
[0117] From the viewpoint of exhibiting reverse wavelength dispersion, k and l are preferably in the range of 2≤k+l≤6, preferably k+l=4, more preferably k=2 and l=2. When k=2 and l=2, a symmetrical structure is obtained, which is further preferred.
[0118] E 1 and E 2 Each independently is preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.
[0119] As P 1 or P 2 The polymerizable group represented by , for example, epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, and the like can be mentioned. Among these, acryloyloxy, methacryloyloxy, vinyloxy, oxirane, and oxirane are preferred, and acryloyloxy is more preferred.
[0120] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, benzene ring, naphthalene ring, anthracene ring, etc. can be enumerated, preferably benzene ring, naphthalene ring. As the aromatic heterocycle, furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole ring, oxazole ring, benzoxazole ring, and phenanthroline ring, etc. can be enumerated. Among these, preferably have thiazole ring, benzothiazole ring or benzofuran ring, further preferably have benzothiazole ring. In addition, when Ar contains nitrogen atom, the nitrogen atom preferably has π electrons.
[0121] In formula (I), the total number of π electrons N contained in the divalent aromatic group represented by Ar is π It is preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.
[0122] Examples of the aromatic group represented by Ar include groups of the following formulae (Ar-1) to (Ar-23).
[0123]
[0124] In the formulas (Ar-1) to (Ar-23), the symbol * represents a connecting portion, and Z 0 , Z 1 and Z 2 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.
[0125] Q 1 and Q 2 Each independently represents -CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -, -CO- or -O-, R 2’ and R 3’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0126] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.
[0127] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.
[0128] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom, and m represents an integer of 0-6.
[0129] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, and biphenyl, preferably phenyl and naphthyl, and more preferably phenyl. The aromatic heterocyclic group includes aromatic heterocyclic groups having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl, and preferably furanyl, thienyl, pyridyl, thiazolyl, and benzothiazolyl.
[0130] Y 1 and Y 2 Each independently may be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring collection. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring collection.
[0131] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferred are a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group and a cyano group.
[0132] Q 1 and Q 2 Preferred are -NH-, -S-, -NR 2’ -、-O-,R 2’ A hydrogen atom is preferred, and -S-, -O-, and -NH- are particularly preferred.
[0133] Among formulae (Ar-1) to (Ar-23), formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0134] In the formulas (Ar-17) to (Ar-23), Y 1 The nitrogen atom and Z to which it can be bonded 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic groups described above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. The aromatic heterocyclic group may have a substituent. In addition, Y 1 The nitrogen atom and Z to which it can be bonded 0 Together, they form the aforementioned substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. Examples thereof include benzofuran ring, benzothiazole ring, benzoxazole ring, etc. It should be noted that the compounds represented by the above formulas (Ar-1) to (Ar-23) can be prepared, for example, by the method described in Japanese Patent Publication No. 2010-31223.
[0135] The content of the polymerizable liquid crystal compound (A) in the polymerizable liquid crystal composition (A) constituting the phase difference layer is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, and more preferably 90 to 98 parts by mass, relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition (A). When the content is within the above range, there is a tendency for the orientation of the phase difference plate to be improved. Here, the so-called solid component refers to the total amount of components after removing volatile components such as solvents from the polymerizable liquid crystal composition (A).
[0136] The polymerizable liquid crystal composition (A) may contain a polymerization initiator for initiating a polymerization reaction of the polymerizable liquid crystal compound (A). In addition, the polymerizable liquid crystal composition (A) may contain a photosensitizer, a leveling agent, an additive, and the like as necessary.
[0137] As for the phase difference layer, for example, a solvent can be added to a polymerizable liquid crystal composition (A) containing a polymerizable liquid crystal compound (A) and a polymerization initiator, additives, etc. added as needed, and a composition (hereinafter also referred to as a "phase difference film forming composition") can be prepared by mixing and stirring, and the composition is applied to a substrate or an oriented film, and the solvent is removed by drying, and the polymerizable liquid crystal compound (A) in the obtained coating is cured by heating and / or active energy rays to obtain a phase difference film.
[0138] The substrate is preferably a transparent substrate. The oriented film is formed by aligning the polymerizable liquid crystal compound contained in the phase difference film forming composition in any direction. The oriented film can be formed of an oriented polymer. In addition, the oriented film can be a photo-oriented film.
[0139] As the oriented polymer, for example, polyamides having amide bonds in the molecule, gelatins, polyimides having imide bonds in the molecule and polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylate as their hydrolyzates can be cited. Among them, polyvinyl alcohol is preferred. The oriented polymer can be used alone or in combination of two or more.
[0140] As for the oriented film containing the oriented polymer, it can be obtained by the following method: applying the composition obtained by dissolving the oriented polymer in a solvent (hereinafter, sometimes referred to as "oriented polymer composition") on the substrate and removing the solvent; or applying the oriented polymer composition on the substrate, removing the solvent, and rubbing (rubbing method). As a solvent, any substance that can dissolve the components constituting the oriented polymer composition can be used, for example, it can be appropriately selected from the following: aliphatic hydrocarbons such as hexane and octane; aromatic hydrocarbons such as toluene and xylene; alcohols such as ethanol, 1-propanol, isopropanol, and 1-butanol; ketones such as methyl ethyl ketone and methyl isobutyl ketone; esters such as ethyl acetate, butyl acetate, and isobutyl acetate; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether; esterified glycol ethers such as ethylene glycol monomethyl ether acetate and propylene glycol monomethyl ether acetate, etc.
[0141] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer material can be completely dissolved in the solvent, and is preferably about 0.1 to 20%, more preferably about 0.1 to 10%, in terms of solid content relative to the solution.
[0142] As the oriented polymer composition, a commercially available oriented film material may be used as it is. Examples of commercially available oriented film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and OPTMER (registered trademark, manufactured by JSR Corporation).
[0143] Examples of a method for coating the oriented polymer composition on a substrate include known methods such as coating methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and coater coating, and printing methods such as offset coating.
[0144] Examples of a method for removing the solvent contained in the oriented polymer composition include a natural drying method, a ventilation drying method, a heat drying method, and a reduced pressure drying method.
[0145] In order to provide an alignment control force to the alignment film, a rubbing treatment (rubbing method) may be performed as needed.
[0146] As a method of imparting an orientation control force by rubbing, there can be mentioned a method of bringing an oriented polymer film formed on the surface of a substrate by applying an oriented polymer composition to a substrate and annealing the oriented polymer film into contact with a rubbing roller wound with a rubbing cloth and rotating.
[0147] The photo-alignment film can be generally obtained by applying a composition comprising a polymer or monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film-forming composition") on a substrate and irradiating the substrate with polarized light (preferably polarized UV light). In the case of the photo-alignment film, it is more preferable that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0148] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by light irradiation. Specifically, groups that participate in the photoreaction of the orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules that occur by light irradiation, which become the source of liquid crystal orientation ability, can be cited. Among them, from the aspect of excellent orientation, groups that participate in dimerization reaction or photocrosslinking reaction are preferred. As a photoreactive group, a group having an unsaturated bond, especially a double bond, is preferably a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond).
[0149] As photoreactive groups having C=C bonds, vinyl, polyene, stilbene, stilbazole, stilbazolium, chalcone, and cinnamoyl groups can be cited. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, azophenyl, azonaphthyl, aromatic heterocyclic azo, bisazo, formazan, and groups having an oxidized azobenzene structure can be cited. As photoreactive groups having C=O bonds, benzophenone, coumarin, anthraquinone, and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and halogenated alkyl.
[0150] Among them, photoreactive groups that participate in the photodimerization reaction are preferred, and cinnamoyl and chalcone groups are preferred from the perspective of a small amount of polarized light irradiation required for photo-alignment and the ease of obtaining a photo-alignment film with excellent thermal stability and temporal stability. As a polymer having a photoreactive group, a polymer having a cinnamoyl group such that the terminal portion of the polymer side chain becomes a cinnamic acid structure is particularly preferred.
[0151] By applying the composition for forming a photo-alignment film on a substrate, a photo-alignment layer can be formed on the substrate. As the solvent contained in the composition, the same solvent as the solvent used in the composition for forming an alignment film and exemplified above can be cited, and it can be appropriately selected according to the solubility of the polymer or monomer having a photoreactive group.
[0152] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted according to the type of the polymer or monomer and the thickness of the target photo-alignment film, and is preferably at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass, relative to the mass of the composition for forming a photo-alignment film. The composition for forming a photo-alignment film can contain a polymer material such as polyvinyl alcohol and polyimide, and a photosensitizer within a range that does not significantly impair the properties of the photo-alignment film.
[0153] As a method for applying the photo-alignment film-forming composition to a substrate, the same method as the method for applying the alignment composition to a substrate can be cited. As a method for removing the solvent from the applied photo-alignment film-forming composition, for example, natural drying, ventilation drying, heating drying, and reduced pressure drying can be cited.
[0154] In order to irradiate polarized light, it can be a form of directly irradiating polarized UV light to the product obtained after removing the solvent from the composition for forming a photo-alignment film applied on the substrate, or it can be a form of irradiating polarized light from the substrate side and allowing the polarized light to pass through. In addition, it is particularly preferred that the polarized light is substantially parallel light. The wavelength of the irradiated polarized light is preferably a wavelength in the wavelength region where the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) in the range of 250 to 400nm is particularly preferred. As the light source used in the polarized light irradiation, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because the luminous intensity of ultraviolet rays with a wavelength of 313nm is large. Polarized UV light can be irradiated by irradiating the light from the above-mentioned light source through an appropriate polarizer. As the polarizer, a polarizing filter, a polarizing prism such as a Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0155] It should be noted that, by shielding during rubbing or polarized light irradiation, a plurality of regions (patterns) in which the directions of liquid crystal alignment are different can be formed.
[0156] The groove oriented film is a film having a concave-convex pattern or multiple grooves (grooves) on the film surface. When a polymerizable liquid crystal compound is applied to a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules will be oriented in the direction along the grooves.
[0157] As methods for obtaining a grooved oriented film, there are: a method of exposing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape, and then developing and rinsing to form a concave-convex pattern; a method of forming a layer of a UV-curable resin before curing on a plate-like original plate having grooves on its surface, transferring the formed resin layer to a substrate, and then curing it; and a method of pressing a roll-shaped original plate having a plurality of grooves against a film of a UV-curable resin before curing formed on a substrate to form convex-concave and concave, and then curing it; and the like.
[0158] The thickness of the alignment film (alignment film or photoalignment film containing an aligning polymer) is usually in the range of 10 to 10000 nm, preferably 10 to 1000 nm, more preferably 500 nm or less, further preferably 10 to 200 nm, particularly preferably 50 to 150 nm.
[0159] Examples of a method for applying the retardation film-forming composition to a substrate include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and coater coating, and printing methods such as offset printing.
[0160] Next, under the condition that the polymerizable liquid crystal compound contained in the coating film obtained from the phase difference film forming composition does not polymerize, the solvent is removed by drying or the like, thereby forming a dried coating film. Examples of the drying method include natural drying, ventilation drying, heating drying, and reduced pressure drying.
[0161] In addition, in order to make the polymerizable liquid crystal compound phase transition to the liquid phase, the temperature is raised to a temperature above the temperature at which the polymerizable liquid crystal compound phase transitions to the liquid phase, and then the temperature is lowered to make the polymerizable liquid crystal compound phase transition to the nematic phase. The phase transition can be performed after removing the solvent in the above-mentioned coating film, or it can be performed simultaneously with the removal of the solvent.
[0162] By polymerizing the polymerizable liquid crystal compound while maintaining the nematic liquid crystal state of the polymerizable liquid crystal compound, a solidified layer, i.e., a phase difference layer, of the polymerizable liquid crystal composition is formed. As a polymerization method, photopolymerization is preferred. In photopolymerization, as the light irradiated to the dry coating, the type of photopolymerization initiator contained in the dry coating, the type of polymerizable liquid crystal compound (especially the type of polymerizable group possessed by the polymerizable liquid crystal compound) and its amount are appropriately selected. As a specific example thereof, one or more light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays, and active electron rays can be cited. Among them, from the aspect of easily controlling the progress of the polymerization reaction and being able to use a device widely used in the art as a photopolymerization device, ultraviolet light is preferred, and preferably the type of polymerizable liquid crystal compound and photopolymerization initiator contained in the polymerizable liquid crystal composition is pre-selected in a manner that can be photopolymerized by ultraviolet light. In addition, it is also possible to irradiate light while cooling the dry coating using appropriate cooling means during polymerization, thereby controlling the polymerization temperature.
[0163] If the polymerizable liquid crystal compound is polymerized at a lower temperature by using such cooling means, a polarizing plate can be formed appropriately even if a substrate with low heat resistance is used. A patterned phase difference plate can also be obtained by shielding, developing, etc. during photopolymerization.
[0164] As the light source of the above-mentioned active energy rays, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, and the like.
[0165] UV radiation intensity is usually 10 to 3,000 mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in the wavelength region effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and further preferably 10 seconds to 1 minute. When irradiating once or multiple times with such ultraviolet irradiation intensity, the cumulative light amount is 10 to 3,000 mJ / cm 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 .
[0166] The thickness of the retardation layer can be appropriately selected depending on the display device to which it is applied, and is preferably 0.1 to 10 μm, more preferably 1 to 5 μm, and even more preferably 1 to 3 μm from the viewpoint of thinning and flexibility.
[0167] <Optical compensation plate>
[0168] The laminate for organic EL display of the present invention may be further combined with an optical compensation plate as required. The optical compensation plate has an optical function of compensating for the viewing angle and color of a liquid crystal display device, and is preferably formed by aligning a liquid crystal substance.
[0169] The optical compensation plate is more preferably formed of a polymer of a polymerizable liquid crystal compound and satisfies the following formula (5):
[0170] -30nm≤Rth(550)≤-100nm (5)
[0171] (Rth(550) represents the in-plane phase difference in the film thickness direction when irradiated with a wavelength of 550 nm.)
[0172] As liquid crystal substances preferably used in such optical compensation plates, side chain type liquid crystal polymer compounds can be cited. Side chain type liquid crystal polymer compounds are formed by bonding the mesogen groups of the core unit presenting the liquid crystal layer to the flexible main chain in the form of side chains via flexible chains. For example, polyacrylate, polymethacrylate, polysiloxane, etc. can be cited as the main chain skeleton, and as required, a substance having a mesogen group as a side chain via a spacer formed by a conjugated atomic group, etc. In addition, in order to control the tensile elastic modulus of the film, the end on the opposite side of the main chain from the mesogen group of the side chain can have a polymerizable functional group such as an oxetane group, an epoxy group, a vinyl ether group, etc. for crosslinking via a spacer formed by a conjugated atomic group, etc. as required.
[0173] The thickness of the optical compensation plate is, for example, about 0.1 to 30 μm, preferably about 0.5 to 25 μm, and more preferably about 3 to 20 μm.
[0174] <Circularly polarizing plate>
[0175] The circular polarizing plate in the present invention comprises a polarizing plate and a phase difference plate, and the polarizing plate comprises a polarizer and a protective film. The polarizing plate has a protective film on the side opposite to the phase difference plate.
[0176] In the circularly polarizing plate, the polarizing plate and the phase difference plate may be laminated via an adhesive layer or a pressure-sensitive adhesive layer, preferably laminated via a pressure-sensitive adhesive layer. That is, the circularly polarizing plate preferably has a structure in which the polarizing plate, the pressure-sensitive adhesive layer and the phase difference plate are laminated in this order.
[0177] As the pressure-sensitive adhesive layer for laminating the polarizing plate and the retardation plate, a pressure-sensitive adhesive layer having a transmittance of 10% or less at a wavelength of 400 nm (hereinafter, sometimes referred to as a near-infrared absorbing pressure-sensitive adhesive layer) is preferred.
[0178] The adhesive composition for forming the adhesive layer for laminating the polarizing plate and the phase difference plate is not particularly limited, and a known adhesive composition can be used.
[0179] The adhesive composition for forming the near-infrared absorbing adhesive layer is not particularly limited. For example, the adhesive composition described in Japanese Patent Gazette No. 2017-119700 can be cited. Preferably, it is an adhesive composition comprising a compound that selectively absorbs light with a wavelength near 400 nm (for example, a wavelength of 385 nm to a wavelength of 405 nm), and more preferably, it is an adhesive composition comprising a light selective absorption compound having a merocyanine structure.
[0180] The water vapor transmission rate of the circularly polarizing plate of the present invention is 100 g / m 2 / 24 hours or less, and the transmittance of light at 380 nm is 1% or less. Thus, an organic EL display having excellent display characteristics, bendability and aging degradation can be obtained.
[0181] The water vapor transmission rate was measured according to JIS Z 0208 at 40°C and 90% relative humidity, with the water vapor transmission rate per m 2 The water vapor permeability is calculated based on the membrane area and the amount of water that passes through the membrane within 24 hours. 2 / 24 hours, the durability of the obtained organic EL display deteriorates. The water vapor transmission rate is preferably 60g / m 2 / 24 hours or less, more preferably 30g / m 2 / 24 hours or less, more preferably 10g / m 2 / 24 hours or less, and the water vapor transmission rate may be as low as the measurement limit.
[0182] Regarding the light transmittance, the transmittance at 380 nm is measured using a spectrophotometer (UV-3150; manufactured by Shimadzu Corporation). More preferably, the transmittance at both 380 nm and 400 nm is determined. The transmittance at these wavelengths is preferably 0.5% or less, more preferably 0.3% or less.
[0183] The circularly polarizing plate preferably has an oxygen permeability of 30 cc / atm / m 2 / Less than 24 hours.
[0184] The oxygen permeability is measured based on JIS K 7126 using an oxygen permeability measuring device (OX-TRANML, manufactured by MOCON) at 23°C and a relative humidity of 50%. In order to further improve the durability of the organic EL display, the oxygen permeability is more preferably 20 cc / atm / m 2 / 24 hours or less, more preferably 10cc / atm / m2 / Less than 24 hours.
[0185] <Adhesive Layer (1)>
[0186] In the present invention, the adhesive composition used to form an adhesive layer laminated with a circular polarizing plate (in this specification, the adhesive layer is sometimes referred to as "adhesive layer (1)".) is not particularly limited, and for example, suitable adhesives such as acrylic, silicone, polyester, polyurethane, polyamide, polyether, and rubber can be used. Among them, pressure-sensitive acrylic adhesives are preferred from the perspectives of optical transparency, adhesive properties, weather resistance, etc. The adhesive layer (1) is usually laminated on the phase difference plate of the circular polarizing plate. On the side of the adhesive layer (1) opposite to the surface laminated with the circular polarizing plate, other layers (diaphragms, etc.) can be further laminated.
[0187] It should be noted that the adhesive layer (1) and the adhesive layer used in laminating the polarizing plate and the phase difference plate can be given functionality according to the application, such as dispersing various diffusing agents to impart diffusibility, or mixing various conductive substances to impart antistatic properties.
[0188] The thickness of the laminated body in which the circularly polarizing plate and the pressure-sensitive adhesive layer are laminated is preferably 100 μm or less, and more preferably 90 μm or less, from the viewpoint of the bendability and visibility of the display device.
[0189] <Organic EL display device (organic EL display)>
[0190] The present invention includes a display device including the laminate for an organic EL display of the present invention.
[0191] As display devices, liquid crystal display devices, organic electroluminescent (EL) display devices, inorganic electroluminescent (EL) display devices, touch panel display devices, electron emission display devices (field emission display devices (FED, etc.), surface field emission display devices (SED)), electronic paper (display devices using electronic ink, electrophoretic elements), plasma display devices, projection display devices (grating light valve (GLV) display devices, display devices with digital micromirror devices (DMD), etc.) and piezoelectric ceramic displays can be cited. Liquid crystal display devices include any of transmission type liquid crystal display devices, semi-transmission type liquid crystal display devices, reflection type liquid crystal display devices, direct view type liquid crystal display devices and projection type liquid crystal display devices. These display devices can be display devices that display two-dimensional images, or they can be stereoscopic display devices that display three-dimensional images. In particular, as the display device of the present invention, organic EL display devices and touch panel display devices are preferred, and organic EL display devices are particularly preferred.
[0192] Example
[0193] Hereinafter, the present invention will be described in further detail using Examples and Comparative Examples. "%" and "parts" in Examples and Comparative Examples mean "mass %" and "mass parts" unless otherwise specified.
[0194] [Example 1]
[0195] <Production of polarizing plate>
[0196] [Polarizing plate: Manufacturing of iodine PVA type polarizing plate]
[0197] A polyvinyl alcohol film (PVA: average degree of polymerization of about 2400, degree of saponification of 99.9 mol% or more) with a thickness of 30 μm was uniaxially stretched by dry stretching for about 5 times, and then immersed in pure water at 40°C for 40 seconds while maintaining a tightened state. Then, it was immersed in a dyeing aqueous solution with a mass ratio of iodine / potassium iodide / water of 0.044 / 5.7 / 100 at 28°C for 30 seconds for dyeing. Next, it was immersed in a boric acid aqueous solution with a mass ratio of potassium iodide / boric acid / water of 11.0 / 6.2 / 100 at 70°C for 120 seconds. Next, it was washed with pure water at 8°C for 15 seconds, and then dried at 60°C for 50 seconds while maintaining a tension of 300N, and then dried at 75°C for 20 seconds to obtain a polarizer with a thickness of 12 μm in which iodine was adsorbed and oriented in the polyvinyl alcohol film.
[0198] A water-based adhesive was injected between the obtained polarizer and the cycloolefin film (ZF14 manufactured by ZEON Co., Ltd., Japan), and the laminate was performed with a clamping roller. The obtained laminate was dried at 60°C for 2 minutes while the tension was maintained at 430 N / m to obtain a polarizing plate I having a cycloolefin film (COP) as a protective film on one side. It should be noted that the water-based adhesive was prepared by adding 3 parts of carboxyl-modified polyvinyl alcohol (Kuraray Poval KL318; manufactured by Kuraray Co., Ltd.) and 1.5 parts of a water-soluble polyamide epoxy resin (Sumirez Resin 650; manufactured by Sumika Chemtex Co., Ltd., an aqueous solution with a solid content concentration of 30%) to 100 parts of water.
[0199] <Production of Phase Difference Plate>
[0200] [Preparation of Photo-Alignment Film-Forming Composition]
[0201] 5 parts of the following photo-alignment material described in JP-A-2013-033249 and 95 parts of cyclopentanone (solvent) were mixed, and the obtained mixture was stirred at 80° C. for 1 hour to obtain a composition for forming a photo-alignment film.
[0202] (Photo-oriented materials)
[0203]
[0204] [Preparation of polymerizable liquid crystal composition]
[0205] The polymerizable liquid crystal compound A-1 (86.0 parts) of the following structure, the polymerizable liquid crystal compound A-2 (14.0 parts), the polyacrylate compound (leveling agent / BYK-361N; manufactured by BYK-Chemie) (0.12 parts) and 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone (photopolymerization initiator / Irgacure369; manufactured by Ciba Specialty Chemicals) (3.0 parts) are mixed to obtain a polymerizable liquid crystal composition (A1) containing the polymerizable liquid crystal compound A-1 and the polymerizable liquid crystal compound A-2.
[0206] Polymerizable liquid crystal compound A-1:
[0207]
[0208] Polymerizable liquid crystal compound A-2:
[0209]
[0210] [Production of phase difference plate]
[0211] A cycloolefin polymer film (COP; ZF-14; manufactured by ZEON Corporation) was treated once using a corona treatment device (AGF-B10; manufactured by Kasuga Electric Co., Ltd.) at an output of 0.3 kW and a treatment speed of 3 m / min. The photo-alignment film-forming composition was applied to the surface subjected to the corona treatment using a bar coater, dried at 80° C. for 1 minute, and irradiated with a polarized UV light device (SPOT CURE SP-7 with a polarizer unit; manufactured by Ushio Electric Co., Ltd.) at a rate of 100 mJ / cm 2 Polarized UV light exposure was performed with an accumulated light amount of 1000 nm to form an alignment film. The thickness of the obtained alignment film was measured with an ellipsometer M-220 (manufactured by JASCO Corporation) and found to be 100 nm.
[0212] Next, the polymerizable liquid crystal composition (A1) containing a polymerizable liquid crystal compound prepared previously was applied to the above-mentioned alignment film under the condition that the wire of the bar coater was set to #30 and the speed was 50 mm / second, and dried at 120°C for 1 minute. Then, a high-pressure mercury lamp (Unicure VB-15201BY-A; manufactured by Ushio Electric Co., Ltd.) was used to irradiate ultraviolet rays from the side of the surface coated with the polymerizable liquid crystal composition (A1) (in a nitrogen atmosphere, the cumulative light amount at a wavelength of 313 nm: 500 mJ / cm2 ), thereby forming a laminate of a phase difference layer and a cycloolefin polymer film. The thickness of the obtained phase difference layer was measured with a laser microscope (LEXT; manufactured by Olympus Corporation) and found to be 2.3 μm.
[0213] The retardation value of the obtained retardation layer at a wavelength of 550 nm was measured and found to be Re(550)=140 nm.
[0214] The retardation values of the obtained retardation layer at a wavelength of 450 nm and a wavelength of 650 nm were measured, and the results were Re(450) / Re(550)=0.85 and Re(650) / Re(550)=1.05.
[0215] <Production of Circular Polarizing Plate>
[0216] Using an adhesive (manufactured by Lintec Co., Ltd., acrylic adhesive (colorless, transparent, non-oriented), polarizing plate I and phase difference plate B were bonded together in such a way that the angle (θ) formed by the absorption axis of polarizing plate I and the slow axis of phase difference plate B was 45°, and then the cycloolefin polymer film of the phase difference plate was peeled off to prepare circular polarizing plate 1.
[0217] <Production of Laminated Body for Organic EL Display>
[0218] An acrylic adhesive (manufactured by Lintec Corporation, film thickness: 15 μm) was laminated on the obtained retardation plate of the circularly polarizing plate to obtain a laminate for an organic EL display.
[0219] Table 1 summarizes the layer structures of the obtained laminated body for an organic EL display.
[0220] <Measurement of water vapor transmission rate>
[0221] The obtained circularly polarizing plate was measured at 40°C and 90% relative humidity in accordance with JIS Z 0208, and the relative humidity per 1m 2 The results are shown in Table 2: membrane area and the amount of water passing through the membrane in 24 hours.
[0222] <Determination of oxygen permeability>
[0223] The obtained circularly polarizing plate was measured at 23° C. and a relative humidity of 50% using an oxygen transmission rate measuring apparatus (OX-TRANML, manufactured by MOCON) in accordance with JIS K7126.
[0224] <Measurement of transmittance>
[0225] The transmittance of the obtained circularly polarizing plate at 380 nm and 400 nm was measured using a spectrophotometer (UV-3150; manufactured by Shimadzu Corporation).
[0226] <Weather resistance test>
[0227] The acrylic adhesive of the obtained laminate for organic EL display was bonded to the display device obtained by removing the front glass and polarizing plate from the "Galaxy S5" manufactured by SAMSUNG. The reflected hue was confirmed when the power of the display device was set to the off state (black display) and the on state (white display). The results of the initial appearance and the appearance after the 100-hour accelerated weathering test in the sunshine weather meter (100-hour accelerated weathering test) are shown in Table 3. It should be noted that the front reflection hue ("white display" and "black display" in Table 3) is the hue obtained by visually observing the sample from the front at a distance of 50 cm to confirm the hue, and the oblique reflection hue ("oblique black display" in Table 3) is the hue when the sample is visually observed from an elevation angle of 60° and an azimuth angle of 0 to 360° at a distance of 50 cm.
[0228] <Flexibility Test>
[0229] A glass plate with a thickness of 0.7 mm was placed on the coating surface side of the obtained circularly polarizing plate, and the laminate was bent 180 degrees in a manner lying on the glass plate, and then the bent portion was observed through the light of a fluorescent lamp with a magnifying glass of 10 times to confirm whether there were wrinkles or cracks. The case where no wrinkles or cracks were observed was set as A, the case where wrinkles were slightly confirmed was set as B, and the case where wrinkles and cracks were observed was set as C. The results are shown in Table 3.
[0230] [Example 2]
[0231] The same method as in Example 1 was used except that the adhesive between the polarizing plate and the phase difference plate in Example 1 was changed to the adhesive (near-ultraviolet PSA) described in Example 2 of Japanese Patent Application Publication Gazette JP-A-2017-120430.
[0232] [Example 3]
[0233] [Production of phase difference plate]
[0234] <Preparation of Oriented Polymer Composition (1)>
[0235] Water was added to commercially available polyvinyl alcohol (polyvinyl alcohol 1000 completely saponified type, manufactured by Wako Pure Chemical Industries, Ltd.) and heated at 100°C for 1 hour to obtain an oriented polymer composition (1). The solid content in the oriented polymer composition (1) was 2% by mass.
[0236] <Preparation of Composition (B-1)>
[0237] The polymerizable liquid crystal compound represented by formula (LC242), a polymerization initiator (manufactured by BASF; Irgacure907), a polyacrylate compound (leveling agent / BYK-361N; manufactured by BYK-Chemie), a reaction additive (Laromer (registered trademark) LR-900 manufactured by BASF) and propylene glycol 1-monomethyl ether 2-acetate (PGMEA) were mixed to obtain a composition (B-1). It should be noted that the proportions of the various compounds in the composition (B-1) were 19.2% by mass of the polymerizable liquid crystal compound, 0.5% by mass of the polymerization initiator, 0.1% by mass of the leveling agent, 1.1% by mass of the reaction additive and 79.1% of PGMEA.
[0238]
[0239] <Production of Phase Difference Layer 1>
[0240] After applying the oriented polymer composition (1) on a saponified triacetyl cellulose film (hereinafter sometimes referred to as TAC) and heating and drying, an oriented polymer film with a thickness of 80 nm was obtained. The surface of the obtained oriented polymer film was subjected to a friction treatment. Using a rod coater, the composition (B-1) was applied thereon, dried at 100°C for 1 minute, and then irradiated with ultraviolet light using a high-pressure mercury lamp (under a nitrogen atmosphere, the cumulative light amount at a wavelength of 365nm: 1200mJ / cm 2 ), thereby forming a phase difference layer 1. The film thickness of the phase difference layer 1 obtained was measured using a laser microscope, and the result was 1.94μm. The phase difference value of the phase difference layer 1 obtained was measured, and the result was Re(550)=269nm. In addition, the phase difference values at a wavelength of 450nm and a wavelength of 650nm were measured, and the results were Re(450) / Re(550)=1.08, and Re(650) / Re(550)=0.99.
[0241] <Production of Phase Difference Layer 2>
[0242] The oriented polymer composition (1) was applied to a saponified triacetyl cellulose film (manufactured by Konica Minolto Co., Ltd., KC4UY) and heated and dried to obtain an oriented polymer film with a thickness of 82 nm. The surface of the obtained oriented polymer film was subjected to a rubbing treatment at an angle of 15° to the longitudinal direction of TAC, and the composition (B-1) was applied thereon using a bar coater, dried at 100°C for 1 minute, and then irradiated with ultraviolet rays using a high-pressure mercury lamp (in a nitrogen atmosphere, the cumulative light amount at a wavelength of 365 nm: 1200 mJ / cm 2 ), thereby forming a phase difference layer 2. The film thickness of the phase difference layer 2 obtained was measured using a laser microscope, and the result was 973nm. The phase difference value of the phase difference layer 2 obtained was measured, and the result was Re(550)=135nm. In addition, the phase difference values at a wavelength of 450nm and a wavelength of 650nm were measured, and the results were Re(450) / Re(550)=1.07 and Re(650) / Re(550)=0.98.
[0243] <Lamination of Phase Difference Layer 1 and Phase Difference Layer 2>
[0244] The phase difference layer 1 and the phase difference layer 2 obtained above were bonded together using a photocurable adhesive so that the angle between the slow axis of the phase difference layer 1 and the slow axis of the phase difference layer 2 was 60°, thereby producing a phase difference plate 3 .
[0245] <Production of Circular Polarizing Plate>
[0246] Using an adhesive, polarizing plate 1 and the phase difference layer 1 side of phase difference plate 3 are bonded together in such a way that the angle (θ) formed by the absorption axis of polarizing plate 1 and the slow axis of phase difference layer 1 is 15°, and the angle (θ) formed by the absorption axis of polarizing plate 1 and the slow axis of phase difference plate 2 is 75°, and then the cycloolefin polymer film of the phase difference plate is peeled off to produce a circularly polarizing plate.
[0247] <Production of Laminated Body for Organic EL Display>
[0248] A laminate for an organic EL display was produced in the same manner as in Example 1 except that the phase difference plate 3 obtained above was used.
[0249] [Example 4]
[0250] [Fabrication of optical compensation plate]
[0251] <Preparation of Oriented Polymer Composition (2)>
[0252] 2-Butoxyethanol was added to SUNEVER SE-610 (manufactured by Nissan Chemical Industries, Ltd.), a commercially available oriented polymer, to obtain an oriented polymer composition (2). The oriented polymer composition (2) had a solid content of 1% by mass.
[0253] The surface of the cycloolefin film was treated once using a corona treatment device at an output power of 0.3 kW and a treatment speed of 3 m / min. The oriented polymer composition (2) was applied to the surface subjected to the corona treatment using a rod coater, and dried at 90°C for 1 minute to obtain an oriented film. The thickness of the oriented film obtained was measured using a laser microscope, and the result was 34 nm. Next, the composition (B-1) was applied to the oriented film using a rod coater, and dried at 90°C for 1 minute, and then irradiated with ultraviolet light using a high-pressure mercury lamp (in a nitrogen atmosphere, the cumulative light intensity at a wavelength of 365 nm: 1000 mJ / cm 2 ), thereby obtaining an optical compensation plate. The film thickness of the obtained optical compensation plate was measured by a laser microscope, and the film thickness was 450nm. In addition, the phase difference value of the obtained optical compensation plate at a wavelength of 550nm was measured, and the result was Re(550)=1nm, Rth(550)=-70nm. It should be noted that the phase difference value of the cycloolefin film itself at a wavelength of 550nm is about 0.
[0254] The circularly polarizing plate prepared in Example 1 and the optical compensation plate obtained above were bonded together using the acrylic adhesive described in Example 1 to obtain a circularly polarizing plate with an optical compensation plate. The acrylic adhesive was further laminated on the optical compensation plate of the circularly polarizing plate with an optical compensation plate to obtain a laminate for an organic EL display.
[0255] [Example 5]
[0256] A 30 μm polyimide film (PI film) was produced by the same method as in Example 1 described in International Publication No. 2017 / 014279.
[0257] The production was carried out in the same manner as in Example 2 except that the polyimide film (PI film) was used as the protective film instead of the cycloolefin polymer film.
[0258] [Example 6]
[0259] A 30 μm polyimide film (PI film) was produced by the same method as in Example 1 described in International Publication No. 2017 / 014279.
[0260] The production was carried out in the same manner as in Example 3 except that the polyimide film was used as the protective film.
[0261] [Example 7]
[0262] A 30 μm polyimide film (PI film) was produced by the same method as in Example 1 described in International Publication No. 2017 / 014279.
[0263] The production was carried out in the same manner as in Example 4 except that the polyimide film was used as the protective film and the adhesive used for laminating the phase difference plate and the polarizing plate was changed to the acrylic adhesive described in Example 1.
[0264] [Comparative Example 1]
[0265] <Production of polarizing plate>
[0266] Triacetyl cellulose film (TAC; KC2UA; manufactured by Konica Minolto Co., Ltd.) is arranged on both sides of the polarizer, and a water-based adhesive is injected between each layer, and the layers are bonded with a clamping roller. While the tension of the obtained bond is maintained at 430 N / m, it is dried at 60°C for 2 minutes to obtain a polarizing plate having triacetyl cellulose film as a protective film on both sides. It should be noted that the above-mentioned water-based adhesive is prepared by adding 3 parts of carboxyl-modified polyvinyl alcohol (Kuraray Poval KL318; manufactured by Kuraray Co., Ltd.) and 1.5 parts of water-soluble polyamide epoxy resin (Sumirez Resin650; manufactured by Sumika Chemtex Co., Ltd., an aqueous solution with a solid content concentration of 30%) to 100 parts of water.
[0267] <Production of Laminated Body for Organic EL Display>
[0268] A laminate for an organic EL display was produced in the same manner as in Example 1 except that a polycarbonate copolymer resin film (WRS-143; manufactured by Teijin Ltd.) was used as the retardation plate.
[0269] [Comparative Example 2]
[0270] A laminate for an organic EL display was produced in the same manner as in Comparative Example 1 except that the phase difference plate 2 produced in Example 3 was used.
[0271] [Comparative Example 3]
[0272] A laminate for an organic EL display was produced in the same manner as in Example 1 except that the polarizing plate produced in Comparative Example 1 was used.
[0273] [Table 1]
[0274]
[0275] It should be noted that "COP" in Table 1 represents a cycloolefin film, "PI" represents polyimide, "TAC" represents a triacetylcellulose film, "PVA" represents polyvinyl alcohol, and "PSA" represents an acrylic adhesive. In addition, Re represents Re (550), α = Re (450) / Re (550), β = Re (650) / Re (550), and Rth represents the in-plane phase difference in the film thickness direction.
[0276] [Table 2]
[0277]
[0278] [Table 3]
[0279]
[0280] From the results of Table 2 and Table 3, it can be seen that for Examples 1 to 7 that meet the requirements of the present invention, the appearance after the 100-hour accelerated weathering test is basically unchanged compared to the initial appearance, and the bendability also maintains the initial performance. For Comparative Examples 1 to 3, the appearance after the 100-hour accelerated weathering test is different from the initial appearance. In particular, the water vapor transmission rate of the comparative examples is 700 g / m 2 / 24 hours, significantly exceeding the benchmark value of 100g / m 2 / 24 hours, so it can be understood that the weather resistance is deteriorating.
Claims
1. A laminate for an organic EL display, comprising a laminate having a circularly polarizing plate and an adhesive layer laminated thereon, The thickness of the laminate is 100 μm or less, The circular polarizer includes a polarizer and a phase difference plate. The polarizing plate includes a polarizer and a protective film, and the protective film is provided only on the side of the polarizer opposite to the side on which the phase difference plate is laminated. The water vapor permeability of the circular polarizer is 100 g / m 2 / 24 hours or less, The transmittance of the circular polarizer at 380nm is less than 1%, and The protective film has a visible light transmittance of 10% or less at 400 nm.
2. The laminate for an organic EL display according to claim 1, in, The polarizer is a polarizer formed of a polyvinyl alcohol-based resin film.
3. The laminate for an organic EL display according to claim 1 or 2, in, The transmittance of the circularly polarizing plate at 400 nm is less than 1%.
4. The laminate for an organic EL display according to claim 1 or 2, in, The phase difference plate comprises only one phase difference layer of a polymer containing a polymerizable liquid crystal compound, and the phase difference plate satisfies all of the following formulas (1), (2) and (3): Re(450) / Re(550)≤1.00 (1) 1.00≤Re(650) / Re(550) (2) 100nm≤Re(550)≤180nm (3) Where Re(λ) represents the in-plane phase difference value with respect to light of wavelength λnm.
5. The laminate for an organic EL display according to claim 4, in, The angle formed by the slow axis of the phase difference plate and the absorption axis of the polarizing plate is substantially 45 degrees.
6. The laminate for an organic EL display according to claim 1 or 2, in, The phase difference plate includes a first phase difference layer and a second phase difference layer in order from the polarizing plate side. The first phase difference layer and the second phase difference layer are each a polymer of a polymerizable liquid crystal compound. The first phase difference layer satisfies the following equation (4): The second phase difference layer satisfies the relationship of formula (3): The phase difference plate satisfies the relationship between equations (1) and (2). Re(450) / Re(550)≤1.00 (1) 1.00≤Re(650) / Re(550) (2) 100nm≤Re(550)≤180nm (3) 200nm≤Re(550)≤300nm (4) Where Re(λ) represents the in-plane phase difference value with respect to light of wavelength λnm.
7. The laminate for an organic EL display according to claim 1 or 2, further comprising an optical compensation plate formed of a polymer of a polymerizable liquid crystal compound satisfying the following formula (5): -30nm≤Rth(550)≤-100nm(5) Rth(550) represents the in-plane phase difference in the film thickness direction with respect to light of a wavelength of 550 nm.
8. The laminate for an organic EL display according to claim 1 or 2, in, The circularly polarizing plate includes an adhesive layer having a transmittance of 10% or less at 400 nm.
9. The laminate for an organic EL display according to claim 1 or 2, in, The protective film is a cycloolefin film.
10. The laminate for an organic EL display according to claim 1 or 2, in, The protective film is a polyimide film or a polyamide-imide film.
11. A circular polarizing plate, wherein at least a polarizing plate, an adhesive layer and a phase difference plate are stacked in this order, The polarizing plate comprises a polarizer and a protective film, and the protective film is provided only on the side of the polarizer opposite to the side on which the phase difference plate is laminated. The phase difference plate satisfies the relationship between equations (1) and (2), The water vapor permeability of the circular polarizer is 100 g / m 2 / 24 hours or less, The transmittance of the circular polarizer at 380nm is less than 1%, and The visible light transmittance of the protective film at 400 nm is less than 10%, Re(450) / Re(550)≤1.00 (1) 1.00≤Re(650) / Re(550) (2).
12. The circularly polarizing plate according to claim 11, in, The polarizer is a polarizer formed of a polyvinyl alcohol-based resin film.
13. The circularly polarizing plate according to claim 11 or 12, in, The transmittance of the circularly polarizing plate at 400 nm is less than 1%.
14. The circularly polarizing plate according to claim 11 or 12, in, The transmittance of the adhesive layer at 400 nm is 10% or less.
15. The circularly polarizing plate according to claim 11 or 12, in, The protective film is a cycloolefin film.
16. The circularly polarizing plate according to claim 11 or 12, in, The protective film is a polyimide film or a polyamide-imide film.
